ASSESSMENT OF THE INVESTMENT POTENTIAL OF NON-BANKING FINANCIAL INSTITUTIONS - Ilchuk, V.P.; Shpomer, T.O.; Shpomer, A.M. (The actual problems of regional economy development, 2023)
The article analyzes existing approaches to the assessment of the investment potential of market entities, which are determined by their role in the investment process: as an object of capital investment, as an investor, and as an entity that combines the functions of an investor and an object of capital investment. In accordance with this fact, the emergence of different types of investment potential is explained, namely «external», which corresponds to entities whose functioning and development depends on external sources of investment, «internal» - which refers to market entities capable of being an investor, and «aggregate», which corresponds to those market entities that combine the functions of attracting funds and investing them. The macro- and micro-environment factors that form the components of «opportunities» and «resources» for all types of investment potential are singled out, while the macro-environment factors characterize the investment climate, and the micro-environment factors - the investment attractiveness of market entities. Thus, the factors of the external environment that determine the investment climate include the following: regulatory and legal field; the state of the investment market, the state of the financial and credit system, the state of currency regulation, the stability of the national currency, etc. And the factors of the internal environment that determine the investment attractiveness of a business entity include: the effectiveness of personnel management, financial resources, partnership relations, prospects for economic growth, etc. The scheme for the formation and use of the aggregate investment potential of non-banking financial institutions (NFIs) has been developed, which shows the functional connections between external and internal investment potentials. The algorithm for assessing the investment potential of NFU is presented. The presence of various methods of assessment of investment potential is noted. It is noted that today there is no single universally recognized method of assessing investment potential, there is no correct combination of qualitative and quantitative indicators of its assessment, which shows the need for further research into the specified problem. In the process of research, it was established that the existing practice of assessing the investment potential of business entities, which combines the functions of attracting investment resources and investing them in other market entities, shows attempts to use various indicators of qualitative and quantitative assessment of investment potential in one methodology, which creates a problem their correct combination for a reliable assessment of the specified potential.